To Fund, to Govern and to Pray. An Aproximation to the Links Between Society, Politics and Religion in Colonial Jujuy (1656-1776) - Estruch, Dolores (2009)
This article analyzes the links between religion, politics and colonial society, and explores the nature of these relations in the concrete practices of the members of the Santísimo Sacramento brotherhood of colonial Jujuy. We focus on the process of construction and legitimation of power, from a perspective that takes into account the interconnections between the sociopolitical and religious dimensions.